1301. Breakthrough Invasive Fungal Infections based on CYP2C19 Levels in Patients Who were on Voriconazole as Primary Antifungal Prophylaxis in Acute Myeloid Leukemia (AML) undergoing Induction Chemotherapy. (31st December 2020) - Singam, Hareesh v; Pasikhova, Yanina; Quilitz, Rod; Greene, John N; Baluch, Aliyah
Abstract: Background: Voriconazole (Vori) is often used for prophylactic anti-fungal therapy in induction chemotherapy for Acute Myeloid Leukemia (AML) patients due to predictable absorption and an extended spectrum antifungal activity. Vori is metabolized predominately by CYP2C19 to metabolites with less antifungal activity. There has been a great interest in understanding CYP2C19 as it significantly affects drug metabolism and pharmacokinetics of numerous drugs including voriconazole. Approximately 39% of patients are genetically predicted to be CYP2C19 ultra-rapid or rapid metabolizers and thus are at an increased risk of breakthrough fungal infection. This study assesses the incidence of breakthrough invasive fungal infections (bIFI) at Moffitt Cancer Center based on CYP2C19 activity. bIFI is defined as new fungal infection while on vori, leading to treatment with liposomal amphotericin B, echinocandin, and/or different triazole. Methods: This is a single-center retrospective analysis of patients who underwent induction chemotherapy for newly diagnosed AML and received voriconazole as the primary antifungal prophylaxis between July 2017 and June 2019. The patients enrolled were over 18 years old and did not have a history of stem cell transplant or solid organ transplant, Human Immunodeficiency Virus, relapsed AML or received systematic antifungal therapy 30 days prior. CYP2C19 were checked for each of the patients between July 2017 to June 2019 who were undergoing induction chemotherapy for newly diagnosed AML. It was checked within one week of admission. The patients were categorized as rapid metabolizers, intermediate metabolizers, normal metabolizers, and unknown CYP2C19. Results: There was an incidence of 20.2% (18/89) bIFI in patients who were on Vori in this study. Of these patients with bIFI infections, 15.7% (3/19) of patients were rapid metabolizers, 14.7% (5/34) were normal metabolizers, 28.5% (4/14) were intermediate metabolizers and 0% (0/3) were poor metabolizers. There were 31% (6/19) breakthrough infections in patients with unknown CYP2C19 characteristics. Conclusion: There is no significant statistical difference (p=0.6) among CYP2C19 categories with respect to breakthrough of invasive fungal infections at Moffitt Cancer Center between July 2017 - June 2019. Disclosures: Rod Quilitz, Pharm D., Astellas (Advisor or Review Panel member)